Genomic analysis of natural intra-specific hybrids among Ethiopian isolates of Leishmania donovani. - James A Cotton; Caroline Durrant; Susanne U Franssen; Tesfaye Gelanew; Asrat Hailu; David Mateus; Mandy J Sanders; Matthew Berriman; Petr Volf; Michael A Miles; Matthew Yeo (PLoS Neglected Tropical Diseases, 2020)
Parasites of the genus Leishmania (Kinetoplastida: Trypanosomatidae) cause widespread and devastating human diseases. Visceral leishmaniasis due to Leishmania donovani is endemic in Ethiopia where it has also been responsible for major epidemics. The presence of hybrid genotypes has been widely reported in surveys of natural populations, genetic variation reported in a number of Leishmania species, and the extant capacity for genetic exchange demonstrated in laboratory experiments. However, patterns of recombination and the evolutionary history of admixture that produced these hybrid populations remain unclear. Here, we use whole-genome sequence data to investigate Ethiopian L. donovani isolates previously characterized as hybrids by microsatellite and multi-locus sequencing. To date there is only one previous study on a natural population of Leishmania hybrids based on whole-genome sequences. We propose that these hybrids originate from recombination between two different lineages of Ethiopian L. donovani occurring in the same region. Patterns of inheritance are more complex than previously reported with multiple, apparently independent, origins from similar parents that include backcrossing with parental types. Analysis indicates that hybrids are representative of at least three different histories. Furthermore, isolates were highly polysomic at the level of chromosomes with differences between parasites recovered from a recrudescent infection from a previously treated individual. The results demonstrate that recombination is a significant feature of natural populations and contributes to the growing body of data that shows how recombination, and gene flow, shape natural populations of Leishmania.